2020
DOI: 10.1177/0972753120987465
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Obesity in India and Its Neurological Implications: A Multifactor Analysis of a Nationwide Cross-Sectional Study

Abstract: Background: India is undergoing a rapid epidemiological transition, from underweight to overweight/obese population. Obesity is a major risk factor in type 2 diabetes and cardiovascular diseases, and is also implicated as a factor in neurological diseases such as Alzheimer’s disease. A robust, pan-Indian estimate of obesity is not yet available. Purpose: This study estimates the pan-Indian prevalence of obesity, stratified across nonmodifiable (age and gender) and modifiable (education and physical activity le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
38
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 38 publications
3
38
0
Order By: Relevance
“…(2014) and found that prevalence of obesity was 15% in middle aged population of Ahmedabad. [7,13] There are studies which have shown the prevalence obstructive sleep apnea in obese individuals, but there is scarcity of such studies in India. So, purpose of this study was to find out prevalence of obstructive sleep apnea among obese individuals by using stop bang questionnaire.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…(2014) and found that prevalence of obesity was 15% in middle aged population of Ahmedabad. [7,13] There are studies which have shown the prevalence obstructive sleep apnea in obese individuals, but there is scarcity of such studies in India. So, purpose of this study was to find out prevalence of obstructive sleep apnea among obese individuals by using stop bang questionnaire.…”
Section: Resultsmentioning
confidence: 99%
“…[6] Prevalence of obesity in India is 40.3%. [7] More than two-thirds of obese people have OSA. Obesity narrows the upper airway, causes upper airway collapsibility, and disrupts the normal physiologic respiratory drive.…”
Section: Introductionmentioning
confidence: 99%
“…Obesity was higher among women than men (41.88% vs. 38.67%), urban than rural (44.17% vs. 36.08%). 4 The prevalence of overweight and obesity in India is increasing faster than the world average. This fast-paced growth has been accompanied by notable increases in the burden of non-communicable diseases (NCDs).…”
Section: Introductionmentioning
confidence: 99%
“…In India, it is estimated that around 40% of the population suffers from obesity, 9.6% from T2DM, and 9 to 53% from NAFLD. 2 3 4…”
Section: Introductionmentioning
confidence: 99%
“…In India, it is estimated that around 40% of the population suffers from obesity, 9.6% from T2DM, and 9 to 53% from NAFLD. [2][3][4] Conservative therapies including exercise, dietary modification, and weight loss medications remain a mainstay component of weight loss and weight maintenance programs but have limited long-term sustainability. Bariatric surgery, despite its proven effectiveness at inducing weight loss and metabolic changes, remains underutilized, with only 1% of eligible patients undergoing surgical intervention for the treatment of obesity.…”
Section: Introductionmentioning
confidence: 99%